Implant therapy on patients treated with oral bisphosphonates - Aris Petros Tripodakis; Georgios Kamperos; Nikolaos Nikitakis; Alexandra Sklavounou-Andrikopoulou (Ariesdue, 2012)
Aim: Bisphosphonates represent a group of drugs with a significant effect on bone structure preventing bone remodelling. They can be administered for the treatment of osteoporosis, Paget's disease, osteogenesis imperfecta, osteopenia and bone metastases. The aim of this study was to discuss the necessary precautions for successful implant therapy on patients treated with per os bisphosphonates. Case reports: Two female patients, both in the seventh decade of life, requested implant therapy. Their medical history was significant for osteoporosis, managed with per os bisphosphonates (Risedronate and Alendronate, respectively), without other risk factors for osteonecrosis. The duration of bisphosphonate administration was 4 years and 2 months respectively. After consultation with the treating physician, the patients stopped the bisphosphonates 3 months before and 3 months after the placement of the implants. The patients received antibiotic coverage for the surgical interventions. The treatment plan was completed uneventfully with placement of fixed prostheses without complications during a 2-year follow-up period. Conclusion: The greatest dental treatment-related risk for patients on bisphosphonate therapy is bisphosphonate-associated osteonecrosis, which presents with exposure of avascular bone of the jaws and, according to the clinical stage, pain, inflammation, fractures and/or extensive osteolysis. Most of reported cases of bisphosphonate-associated osteonecrosis consist of patients on intravenous drug therapy who had undergone dentoalveolar surgery. Patients on per os bisphosphonates may undergo all types of dentoalveolar surgery, including implant placement, as long as the necessary precautions (bisphosphonate discontinuation, antibiotic coverage, meticulous oral hygiene) are taken.